Revised description of the late Miocene Hyaenictitherium namaquensis (Carnivora, Hyaenidae) from As Sahabi (North Africa, Libya). (3rd August 2022) - Iurino, Dawid Adam; Iannucci, Alessio; Conti, Jacopo; Mecozzi, Beniamino; Sardella, Raffaele; Strani, Flavia
ABSTRACT: An updated description and revision of a left hemimandible assigned to Hyaenictitherium namaquensis, a dog-like hyaena from the late Miocene locality of As Sahabi (Libya, North Africa), is here provided. This fossil is part of the historical collection discovered by Carlo Petrocchi, the Italian researcher who excavated the site in the 1930s. The As Sahabi Hyaenictitherium represents the northernmost occurrence of H. namaquensis in Africa and one of the most informative evidence of this species known to date. The hemimandible has been digitised using photogrammetric techniques, morphological and biometric analyses have been carried out taking into account the African record of Hyaenictitherium .